Preparar el terreno - Jean Daniélou (Revue d'anthropologie des connaissances)
This article looks at the role played by a category of actors –the brokers- in the expansion of multinationals. Frequently invisible, their actions are nonetheless crucial in establishing the global connections that enable multinationals to grow and prosper around the world. With this figure, we propose to study the groundwork on which these global connections are built. Our investigation is based on the ethnography of a renewable energy infrastructure development project on Lubang Island in the Philippines. We show that the role of the broker is not only to connect people who are strangers to each other, but also and above all to prepare the ground for the territorialization of multinationals.